Challenges For Dedicated Smoking Cessation Services In Developing Countries - Tadzimirwa, Gamuchirai Y (Department of Medicine, 2021)
Background South Africa, the country ranked as the ‘second most stressful country to live in' has an estimated 7 million smokers. A dedicated smoking cessation clinic established at Groote Schuur Hospital, Cape Town, provides the only clinical service and training centre in the country. Objectives To evaluate the smokers attending the clinic, in order to better understand the requirements of smoking cessation services in resource-limited settings. Methods Demographic and smoking-related data was collected prospectively from all clinic attendees since its inception. Nicotine dependence, depression scores and exhaled carbon monoxide levels were formally evaluated. Consent was provided to review the collected data. Results Ninety-seven smokers were evaluated. Their mean(standard deviation)age 50.9(10.9)years, and 59% (57/97) were male. The median age of smoking initiation was 16(interquartile range(IQR) 8 - 28) with a current median daily consumption of 12(IQR 7-20). Overall men smoked more than women, with a median of 20( cigarettes per day(IQR 10 - 20) v 12( IQR 5 - 20) respectively (p=0.001). The median Fagerström nicotine dependence score was 5(IQR 3 - 7), with scores of 6(IQR 4 - 8) for men and 5(IQR 2 - 7) for women (p=0.06); 50% of smokers had a Fagerström score < 6(low to above-average dependence) and 22% a score of ≥8 (extreme dependence). The median Patient Health Questionnaire9(PHQ-9) depression score was 8(IQR 4 - 11), and 49% of smokers had symptoms of at least minor depression (score ≥10). The clinic could not provide pharmacotherapy. The self-reported quit rate was 28% at median follow up of 22 months(IQR 14 -39). Conclusions In smokers attempting to quit, moderate levels of nicotine dependence coexist with significant depression and anxiety symptoms. These data inform resource allocation and public health strategies, suggesting that in resource-limited smoking cessation services, psychological/behavioural support focusing on depressive symptoms may be a greater priority than simple pharmacotherapy.